A textbook on modern engineering physics - Chakraborty, Amal (Chhaya Prakashani, 2009)
A textbook on modern engineering physics / Chakraborty, Amal. -- Kolkata: Chhaya Prakashani, 2009 539 C426 No. of Copies : 2